Terceiro setor, economia social e economia solidária: laboratório por excelência de inovação social - Vieira, Naldeir dos Santos (2017)
Proposes a conceptual discussion of the approaches on the "third sector", "social economy" and "solidarity economy" and the contribution of their organizations, projects and activities for the development of social innovations. Demonstrates that, despite the differences, the three concepts refer to domains that are actually characterized by the development of social innovations to be communication spaces where one seeks the implementation of projects and practices geared to solving complex social and collective problems, who do not find response by the market and the State.